The Interaction with H-2Dd in cis is Associated with a Conformational Change in the Ly49A NK Cell Receptor - Back, Jonathan; Angelov, Georgi S.; Mariuzza, Roy A.; Held, Werner (Frontiers in Immunology, 2011)
Mouse Natural killer (NK) cells express Ly49 family receptors that recognize major histocompatibility complex class I (MHC-I) molecules. By interacting with MHC-I molecules expressed on other cells (in trans), inhibitory Ly49 receptors prevent the NK cell-mediated killing of normal cells. In addition, some Ly49 receptors have the unusual property to also interact with MHC-I molecules expressed by the NK cell itself (in cis). Cis binding sequesters a significant fraction of the NK cells' Ly49 receptors, reducing the number of receptors available for trans binding. This lowers the threshold at which NK cell activation exceeds inhibition rendering NK cells more sensitive. It is unclear how Ly49 receptors can bind MHC-I in trans and in cis using the same binding site. We have proposed that this is mediated by two distinct conformations of Ly49 receptors. Here we have tested this model by inferring the distance between the ligand-binding domain of Ly49A and the cell membrane using fluorescence resonance energy transfer (FRET). Consistent with the concept, reducing the distance between the ligand-binding domain of Ly49A and the cell membrane, by shortening the Ly49A stalk, resulted in a substantially increased FRET. The co-expression of cognate MHC-I ligand reduced FRET derived from Ly49A variants with a shortened stalk, indicating that cis association alters FRET. Indeed, FRET improved when cis complexes were disrupted using acid-mediated destruction of MHC-I complexes. These data provide direct evidence that the interaction with MHC-I in cis is associated with a conformational change in the Ly49A receptor on the surface of live cells. The novel FRET based approach may be generally applicable to study conformational changes in cell surface receptors.